ASSOCIATION OF HORMONE RECEPTORS WITH RISK FACTORS AMONG BREAST CANCER PATIENTS - Ummara Aslam (Army Medical College Rawalpindi, 2021)
Objective: To compare the risk factors with estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2) status of breast cancer patients.